Auditory neuropathy: A case report and review of literature - Ahsan, Ali Imam; Hasan, Rashedul; Jamal, Nasimul (Bangladesh Journal of Otorhinolaryngology, 2014)
Auditory Neuropathy (AN), also known as Auditory Dyssynchrony(AD) is a very often missed diagnosis in clinical practice. In AN, sound enters the inner ear normally but the transmission of signals from inner ear to brain is impaired. Due to the lack of advanced audiological test facilities in Bangladesh, mostly AN remains undiagnosed. Here we described a 25 years old male, presented with difficulty in understanding speech for last 10 years. On audiologic evaluation, bilateral moderate sensorineural hearing loss was found on Pure tone audiogram (PTA). Speech discrimination scores were poor and disproportionate to his hearing threshold. Presence of Otoacoustic emission (OAE) revealed the normal function of cochlea. Conversely, absence of Auditory brainstem response (ABR) confirmed the definite dysfunction at auditory neural pathway and hence, the diagnosis of AN was confirmed. Since AN is an underdiagnosed condition in Bangladesh, otolaryngologists should be aware of this clinical entity. All the suspected cases should be referred to specialized centers, where advanced audiological facilities are available. DOI: http://dx.doi.org/10.3329/bjo.v19i2.17638 Bangladesh J Otorhinolaryngol 2013; 19(2): 135-139